Sign Language Poetry on Screen: A Case Study of Ella Mae Lentz’s Silence, Oh Painful - Mohit Joshi; Niraja Saraswat (Acta Universitatis Sapientiae: Film and Media Studies)
Film and videography have played crucial roles in the documentation of performing arts. One such case is of sign language poetry (SLP), which materializes as a phenomenon through the polylogics among different media like visuals and the performing body. The ways of representation within these intersecting language systems of the body, camera, lights, etc. determine how SLP is received. This paper focuses on Ella Mae Lentz’s American Sign Language poem Silence, Oh Painful as a case study, and analyses multiple performances of it. Lentz’s own performance of the poem from her presentation at the 1987 National ASL Poetry Conference is the primary site of inquiry. In comparison, Alexis Boardrow Green’s performance of the poem, for her ASL Poetry Discourse Analysis course at UC San Diego, is examined. Current research aims to study sign language poetry as an intermedial phenomenon, and see how changes in the performing body and its visual representation affect the poem’s unfolding in space and time, with focus on Martin Heidegger’s concept of poetizing, Yuri Lotman’s semiotics, and Lars Elleström’s material intermediality. Moreover, the article also probes into how the usage of the two media (video and the performing body) affect the intended artwork. In light of varying performing bodies, the article further questions the autotelic qualities attributed to poetry from a new-critical approach to artworks, and inquires into the possibility of multiple unaffiliated intermedial phenomena branching from similar intentionalities.